Karakteristik Sensoris Cookies Pisang Nipah Pontianak (Musa paradisiaca) dengan Penambahan Tepung Tempe dan Tepung Kepala Ikan Lele - Uliyanti , Uliyanti; Krisna Evania, Maria; Maulina, Fera; Panca Wardanu, Adha (Politeknik Negeri Ketapang, 2024)
This study aims to evaluate the sensory characteristics and consumer preferences of composite formulations made from nipah banana flour, tempe flour, and catfish head flour. The research design utilized a completely randomized design (CRD) with two factors: the proportion of nipah banana flour to tempe flour (100:0; 90:10; 80:20; 70:30) and variations in catfish head flour (0%, 1%, 2%), resulting in 12 experimental units with 2 replications. Evaluations included sensory analysis of texture, color, taste, aroma, and a hedonic test. The results showed color scores ranging from 2.038 to 4.077, aroma from 2.769 to 3.808, taste from 2.538 to 4.231, and texture from 2.731 to 3.731. The most preferred and accepted formulation, based on the hedonic test, was P1 cookies, with a nipah banana flour to tempe flour ratio of 100:0 and no addition of catfish head flour.